Pastoral livestock farming constraints and adaptation strategies in response to institutional reforms in the Sudano-Sahelian zone of West Africa - Ilboudo, Basnewindé; Zaré, Alhassane; Traoré, Innocent Charles Emmanuel; Bondé, Loyapin; Guuroh, Reginald Tang; Ouédraogo, Oumarou (Frontiers in Sustainable Food Systems, 2025)
IntroductionLivestock farming is one of the main socio-economic activities in West Africa, predominantly extensive and reliant on natural rangelands. In Burkina Faso, the pastoral zone creation process began in 1980 to sedentarize livestock farmers, reduce social conflict, and strengthen livestock production. Therefore, these areas were subjected to institutional reforms with direct consequences on pastoralism. This study aimed to analyze the effects of land tenure and protected area governance reforms on the pastoral production system by identifying concomitantly related constraints and adaptation strategies adopted by local communities.MethodsData were collected through analysis of policy documents, and surveys from 280 key informants and household heads related to the pastoral zone of Yallé using individual interviews and focus group discussions. The main information collected included pastoral landscape and the current state of the livestock production system. Data were also taken on pastoral constraints related to land reforms, protected area governance, and alternative adaptation strategies developed to address constraints.Results and discussionThe changes highlighted are the challenge to the pastoral zone and the appropriation of pastureland by other users inducing range shrinkage, inaccessibility to water resources, and farmer-herders conflicts. In response, some livestock farmers drive their herds out of the country, while others illegally graze in protected areas. They also combine socio-professional conversion to support their livelihoods, with atypical transhumance in the rainy season and seek herd feed satisfaction. New forage harvesting techniques, supported by training, and the integration of agriculture into livestock farming are opportunities to promote agropastoralism, more sustainable. Policymakers should ensure that livestock development actions are legally secure and that institutional reforms promote common resource use in pastoral areas. Also, livestock farmers are encouraged to create community structures for coordinated resource management and conflict resolution. Further, State institutions must supervise investor establishment in pastoral zones while preventing private property rights over the land.